Investigação das características moleculares e filogenéticas dos isolamentos de Pythium insidiosum em casos de ceratite - Bruno Maltez Miraglia (2021)
Introduction: Pythium insidiosum is a microorganism phenotypically like fungi with hyphae, but this oomycete belongs to the phylum Straminopila phylogenetically away from true fungi. Using molecular methodologies, isolates of P. insidiosum were placed in three phylogenetic groups according to their geographic distribution. More recently, four phylogenetic groups were reported. Pythium insidiosum can cause serious infections in humans. It can affect the eyes in the form of keratitis and infections of adjacent tissues that threaten not only the eyesight, but also the patient's life. Due to the development of hyphae, infection with this pathogen is often mistaken and misdiagnosed as a fungal infection. Objective: To investigate the molecular and phylogenetic characteristics of the isolates of P. insidiosum recovered from fourteen samples collected in Indian cases of keratitis. Materials and Methods: Fourteen P. insidiosum isolates were evaluated, from which DNA was extracted and then PCR with universal primers was performed. PCR amplification was performed using Internal Transcriber Spacers (ITS) and Cytochrome C Oxidase S subunit II (COXII) primers and subsequently sequenced. Phylogenetic analyzes, using the aligned ITS and COXII sequences, were analyzed by the Neighbor Joining method (MEGAX). Results: Phylogenetic trees using the amplified DNA sequences (ITS and COXII) showed similar results. The DNA sequences from the fourteen analyzed isolates were specifically placed, with high bootstrap support, in group II (Asia, Australia and Africa) and in group IV (Thailand, Israel), according to the current phylogenetic cluster classification of P. insidiosum. Of the fourteen isolates, ten were placed in cluster II, and four of them in cluster IV. Interestingly, none of the isolations were placed in clusters I and III (The Americas). The ten isolates in this study were identified as P. insidiosum, which support the initial hypothesis. As was previously postulated, this study found that the four Indian DNA sequences located in cluster IV represent an entirely new specie. To confirm this finding, further studies based on statistical analysis are needed. Conclusion: Patients with keratitis of rapid clinical progression, resistant to conventional treatment, with the presence of submerged mycelia adhered to the agar should alert clinicians about the possibility of infection caused by P. insidiosum. To identify possible P. insidiosum isolates, molecular techniques must be performed. Molecular and phylogenetic analyses were used in the present study making it possible to identify the etiological agent of keratitis in India as P. insidiosum. In addition, phylogenetic analyses in this and other studies, suggested the possibility of a new species within P. insidiosum complex, which is probably one of the most important contributions of this study.